Quality-of-life results for accelerated partial breast irradiation with interstitial brachytherapy versus whole-breast irradiation in early breast cancer after breast-conserving surgery (GEC-ESTRO): 5-year results of a randomised, phase 3 trial. Issue 6 (June 2018) - Schäfer, Rebekka; Strnad, Vratislav; Polgár, Csaba; Uter, Wolfgang; Hildebrandt, Guido; Ott, Oliver J; Kauer-Dorner, Daniela; Knauerhase, Hellen; Major, Tibor; Lyczek, Jaroslaw; Guinot, Jose Luis; Dunst, Jürgen; et al.
Summary: Background: Previous results from the GEC-ESTRO trial showed that accelerated partial breast irradiation (APBI) using multicatheter brachytherapy in the treatment of early breast cancer after breast-conserving surgery was non-inferior to whole-breast irradiation in terms of local control and overall survival. Here, we present 5-year results of patient-reported quality of life. Methods: We did this randomised controlled phase 3 trial at 16 hospitals and medical centres in seven European countries. Patients aged 40 years or older with 0–IIA breast cancer were randomly assigned (1:1) after breast-conserving surgery (resection margins ≥2 mm) to receive either whole-breast irradiation of 50 Gy with a boost of 10 Gy or APBI using multicatheter brachytherapy. Randomisation was stratified by study centre, tumour type, and menopausal status, with a block size of ten and an automated dynamic algorithm. There was no masking of patients or investigators. The primary endpoint of the trial was ipsilateral local recurrence. Here, we present 5-year results of quality of life (a prespecified secondary endpoint). Quality-of-life questionnaires (European Organisation for Research and Treatment of Cancer QLQ-C30, breast cancer module QLQ-BR23) were completed before radiotherapy (baseline 1), immediately after radiotherapy (baseline 2), and during follow-up. We analysed the data according to treatment received (as-treated population). Recruitment was completed in 2009, and long-term follow-up is continuing. The trial is registered atClinicalTrials.gov, numberNCT00402519 . Findings: Between April 20, 2004, and July 30, 2009, 633 patients had accelerated partial breast irradiation and 551 patients had whole-breast irradiation. Quality-of-life questionnaires at baseline 1 were available for 334 (53%) of 663 patients in the APBI group and 314 (57%) of 551 patients in the whole-breast irradiation group; the response rate was similar during follow-up. Global health status (range 0–100) was stable in both groups: at baseline 1, APBI group mean score 65·5 (SD 20·6) versus whole-breast irradiation group 64·6 (19·6), p=0·37; at 5 years, APBI group 66·2 (22·2) versus whole-breast irradiation group 66·0 (21·8), p=0·94. The only moderate, significant difference (difference of 10–20 points) between the groups was found in the breast symptoms scale. Breast symptom scores were significantly higher (ie, worse) after whole-breast irradiation than after APBI at baseline 2 (difference of means 13·6, 95% CI 9·7–17·5; p<0·0001) and at 3-month follow-up (difference of means 12·7, 95% CI 9·8–15·6; p<0·0001). Interpretation: APBI with multicatheter brachytherapy was not associated with worse quality of life compared with whole-breast irradiation. This finding supports APBI as an alternative treatment option after breast-conserving surgery for patients with early breast cancer. Funding: German Cancer Aid.